2023
DOI: 10.1038/s41598-023-45566-6
|View full text |Cite
|
Sign up to set email alerts
|

New gene signature from the dominant infiltration immune cell type in osteosarcoma predicts overall survival

Liping Gong,
Xifeng Sun,
Ming Jia

Abstract: The immune microenvironment of osteosarcoma (OS) has been reported to play an important role in disease progression and prognosis. However, owing to tumor heterogeneity, it is not ideal to predict OS prognosis by examining only infiltrating immune cells. This work aimed to build a prognostic gene signature based on similarities in the immune microenvironments of OS patients. Public datasets were used to examine the correlated genes, and the most consistent dominant infiltrating immune cell type was identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…In contrast, high expression of PPARG was positively associated with the low-risk score group, which played the role of oncogene, which was consistent with the ndings of previous scholars mentioned above, and further proved the accuracy of the risk model.While the high expression of PDK1 is proportional to the high expression of Macrophages M0 and inversely proportional to the high expression of Macrophages M2, the opposite is true in PPARG. Combined with previous studies by scholars, Shao et al demonstrated that Macrophages M2 has a pro-carcinogenic role in osteosarcoma [30], and the role of Macrophages M0 for osteosarcoma is still unclear [31], therefore, immunotherapy targeting Macrophages M0 and Macrophages M2 may become a promising therapeutic strategy for the treatment of osteosarcoma.…”
Section: Performance Of Risk Modelsmentioning
confidence: 92%
“…In contrast, high expression of PPARG was positively associated with the low-risk score group, which played the role of oncogene, which was consistent with the ndings of previous scholars mentioned above, and further proved the accuracy of the risk model.While the high expression of PDK1 is proportional to the high expression of Macrophages M0 and inversely proportional to the high expression of Macrophages M2, the opposite is true in PPARG. Combined with previous studies by scholars, Shao et al demonstrated that Macrophages M2 has a pro-carcinogenic role in osteosarcoma [30], and the role of Macrophages M0 for osteosarcoma is still unclear [31], therefore, immunotherapy targeting Macrophages M0 and Macrophages M2 may become a promising therapeutic strategy for the treatment of osteosarcoma.…”
Section: Performance Of Risk Modelsmentioning
confidence: 92%